The Effect of Lyophilized and Frozen Umbilical Cord Cryoextract on L929 Cell Culture - Anna Kaverinska; Nadiia Shevchenko; Aleksandr Osetsky; Liudmyla Sukhodub; Viktoriya Lazurenko; Oleksandr Zhelezniakov; Volodymyr Prokopiuk (Innovative Biosystems and Bioengineering)
Background. The human umbilical cord is a promising source of biologically active substances with regenerative properties. However, the potential of lyophilized cryoextract from the umbilical cord for regenerative medicine, which could facilitate storage and transportation, remains unexplored. Therefore, it is important to study the effect of such cryoextracts using a cellular model.